Effect of molybdenum on numbers of Azospirillum on Brachiaria Decumbens production - Miranda, Cesar H. Behling; Seiffert, Nelson F.; Döbereiner, Johanna (Pesquisa Agropecuaria Brasileira, 2014)
Production of dry matter and total N of Brachiaria decumbens cv. Basilisk under a grazing pressure of 2.5 au/ha were increased by 19% and 29% respectively, in response to fertilization with 160 g of Mo/ha, applied as sodium molybdate. The experiment was conducted on a Dark-Red Latosol phase Cerradão fertilized with P, K, Cu, Zn and B, and evaluated between September/82 and April/83. The Azospirillum countings made every 15 days consistently indicated higher numbers of bacters in roots of plants growing in the Mo treatments than in treatments without Mo.